Analyzing the choosing of e-commerce use among fashion small medium enterprise (sme’s) in Indonesia - Yudhistira, Danindra; Aina, Qorri (Journal of Business and Management, 2020)
Abstract. The purpose of this study is to investigate specifically how far the influence of performance expectancy, facility conditions, anxiety, self-efficacy, and habit of fashion SMEs to use e-commerce. The analysis technique used in this study is with assessing at the significance of the data that has been filled in by respondents both partially and simultaneously. The subjects of this study are the owners of fashion SMEs in Indonesia who have opened online shops in Shopee, Tokopedia, Bukalapak, Lazada, Blibli, and Jd.Id. Furthermore, researchers use non-probability sampling in the sampling technique that researchers use with the type of convenience to make it easier for researchers to get a sample. The results of this study indicate that the level of significance simultaneously shows that all independent variables have a significant effect on the dependent variable. However, the research results partially show that only three variables namely performance expectancy, self-efficacy, and habits have a significant influence on SME fashion to use e-commerce. While the rest, the condition of facilities and anxiety have no significant effect.Keywords: Anxiety, Facilitating Condition, Habit, Performance Expectancy, Self-Efficacy, and Use of E-Commerce.